2006
DOI: 10.1002/anie.200600027
|View full text |Cite
|
Sign up to set email alerts
|

Discrete, Multiblock Isotactic–Atactic Stereoblock Polypropene Microstructures of Differing Block Architectures through Programmable Stereomodulated Living Ziegler–Natta Polymerization

Abstract: The past two decades have witnessed dramatic advances in the development of well-defined transition-metal complexes that can function as catalysts for the stereoselective Ziegler-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
105
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 29 publications
0
105
0
Order By: Relevance
“…Busico (15), Coates (16), and Sita (17) have reported group IV catalysts with varying degrees of isospecificity and livingness for the synthesis of iPP block copolymers. Notably, Sita (17) has recently reported the synthesis of elastomeric multiblock polymers with atactic PP and iPP segments. Coates (18) has recently reported a chiral nickel alpha-diimine catalyst that produces di-and elastomeric triblock polypropylenes with isotactic and regioirregular (rPP) PP blocks, controlled by the polymerization temperature.…”
Section: Block Polyolefinsmentioning
confidence: 99%
“…Busico (15), Coates (16), and Sita (17) have reported group IV catalysts with varying degrees of isospecificity and livingness for the synthesis of iPP block copolymers. Notably, Sita (17) has recently reported the synthesis of elastomeric multiblock polymers with atactic PP and iPP segments. Coates (18) has recently reported a chiral nickel alpha-diimine catalyst that produces di-and elastomeric triblock polypropylenes with isotactic and regioirregular (rPP) PP blocks, controlled by the polymerization temperature.…”
Section: Block Polyolefinsmentioning
confidence: 99%
“…In principle, the H 2 -generating (mechanism A) and alkanegenerating (mechanism B) paths could be distinguished by examination of the products: H 2 is an expected byproduct of mechanism A and SiMe 4 , and other saturated alkanes should be observed for mechanism B. For our experiments, the predominate Zr-alkyl species in solution is [(SBI)ZrCH 2 SiMe 3 ] ϩ because of the low levels of initiation, so a major byproduct of mechanism B should be SiMe 4 .…”
Section: Comparison Of B(c6f5)3 and [Cph3][b(c6f5)4] As Activators Formentioning
confidence: 99%
“…Benefits of single-site polymerization include access to a broader range of catalyst structures through rational syntheses, improved control of polymer molecular weight distributions, and compatibility with flexible solution-based polymerization processes. Perhaps more significantly, single-site catalysts enable the discovery and commercial production of novel polyolefin materials, such as ''blocky'' polymers, with unprecedented properties (2)(3)(4). From an academic viewpoint, homogeneous polymerization catalysts offer marvelous opportunities for probing reaction mechanisms and rational design that cannot be achieved with heterogeneous catalysts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…communications. [1,2] These authors had already reported [3] that the (h 5 -pentamethylcyclopentadienyl)Zr-amidinate (Cp à )-{N( t Bu)C(Me)N(Et)}ZrMe 2 (Scheme 1, 1) can be converted by methide abstraction (e.g., with [HMe 2 N(C 6 …”
mentioning
confidence: 99%